Prevalence and covariates of chronic respiratory disorders among middle-aged Bangladeshi people: A rural community-based study - Hassan, Rashidul; Hasan, Iqbal; Khan, Abdullah H. K.; Ali, Liaquat; Nayeem, Jannatul (Lung India, 2025)
Background: The burden of chronic respiratory diseases (CRDs) and their covariates have not yet been investigated in community settings of Bangladesh where the risk of the disorder is fast increasing due to adverse environmental, sociodemographic, and behavioural shifts. Objective: In this study, the prevalence of CRDs and their socioenvironmental and behavioural risk factors have been explored in a rural Bangladeshi community. Methods: A group of 1224 rural Bangladeshi adults, aged 34-65 years, were screened for CRDs using a locally adapted version of the International Study of Asthma and Allergies in Childhood (ISAAC) Questionnaire as well as by tools covering self-reported and/or prescription/medical record-based diagnoses of CRDs. Spirometry (by hand-held portable device) was done among CRD symptom-positive (CRDS+) subjects (n = 742), and individual CRDs [COPD, Bronchial Asthma, and Restrictive Lung Disease (RLD)] were identified following standard guidelines. Some metabolic biomarkers (OGTT, lipid profile, SGPT, and S Creatinine) were assessed among the spirometrically diagnosed CRD cases (n = 142). Results: Based on spirometry, 19% of the non-spirometry tool-based CRD symptom-positive subjects had one or more CRDs. Higher age (P < 0.001), male gender (P < 0.001), lower BMI (P < 0.001), and exposure to cooking fuel-generated smoke (P = 0.003) were found (both on bivariate and multivariate analyses) to be the significant risk factors. The spirometry-positive CRD subjects were found to be distributed almost equally (COPD, 7%; asthma, 5%; and restrictive, 7%). COPD was found to be more common among males than females (72% vs 28%), but females showed more vulnerability to restrictive disorders (61% vs 39%). The two genders did not differ in proportions of asthma. Lower BMI was associated with COPD; on the contrary, people in higher BMI ranges suffered more from asthma and restrictive disorders. COPD was also found to be associated with tobacco smoking (P = 0.05). No significant difference among the three groups was found regarding any metabolic biomarker. Conclusions: About one-fifth of rural Bangladeshi middle-aged people with respiratory symptoms suffer from one or more CRDs. Higher age, male gender, lower BMI, exposure to cooking fuel-generated smoke, and tobacco smoking are the major risk factors of CRDs among rural Bangladeshis with varying contributions to individual diseases.